Relationship between Serum Transforming Growth Factor β1 Concentrations and the Duration of Type 1 Diabetes Mellitus in Children and Adolescents - Katarzyna Zorena; Dorota Raczyńska; Piotr Wiśniewski; Ewa Malinowska; Małgorzata Myśliwiec; Krystyna Raczyńska; Dominik Rachoń (Hindawi Limited, 2013)
The aim of this study was to evaluate the relationship between serum transforming growth factor β1 (TGF-β1) concentrations and the duration of type 1 diabetes mellitus (T1DM) in children and adolescents. One hundred and sixteen patients with T1DM and 19 healthy controls were examined. Serum TGF-β1 concentrations were measured using the cytometric bead array (CBA). A positive association between the time of diabetes duration and higher serum TGF-β1 concentrations was observed. Similarly, the prevalence of microvascular complications, such as retinopathy and nephropathy, increased with the duration of diabetes. Logistic regression analysis showed that serum TGF-β1 concentrations and the duration of the disease are independent risk factors of microangiopathy development. Higher serum TGF-β1 concentrations were associated with a significant risk of microangiopathy development after 10 years of T1DM duration. In the successive years of the disease, the effect was even stronger. The results of our study indicate that serum TGF-β1 concentrations are one of the factors that may have an impact on the progression of vascular complications in children and adolescents with T1DM.